Causality relationship between energy consumption and economic growth in the European Union countries - Younes Gholizadeh (Economics and Econometrics Research Institute (EERI), 2020)
This study presents the causality relationship between energy consumption and economic growth as a scope of Cobb Douglas production function by using Dynamic Panel Data Analysis for 28 European countries in the 1990-2014 period. The Dynamic Panel Data Analysis method proposed in this study considers the real Gross Domestic Production (GDP) as a dependent variable, while Capital, Labor, and Energy Consumption parameters are considered as independent variables. To indicate the causality relation between GDP and Capital, Labor and Energy Consumption parameters, Arellano-Bond autocorrelation test is applied by taking the first difference of the defined parameters. Furthermore, the Generalized Method of Moments (GMM) is used to validate the obtained results of the Arellano-Bond autocorrelation test. The results of this study show that the GDP has a direct relationship with all independent variables-i.e. Capital, Labor, and Energy Consumption. By a predefined value for the increase in these independent variables, each of the dependent variables demonstrates a unique amount of increase.
Keywords: C22; Q20; Q43; Q47; 330; Neoclassic Economy; Cobb-Douglas Production Function; Dynamic Panel Data; Arellano-Bond GMM Method